LAYANAN INFORMASI KARIER TEHNIK e-LEARNING MEMANTAPKAN PILIHAN KARIER SISWA KELAS X SMA - Ismadi, Ismadi (Jurnal Counsellia, 2014)
Seeing a new era in education, namely the introduction of educational reforms that are closely related to the information systems needed in the development of education, then developed a career information service with e-Learning techniques aimed at 1) see the condition of the implementation of career services at SMAN 1 Ponorogo 2) find the implementation models career information with e-Learning techniques 3) look at the effectiveness of career information service with e-Learning techniques. Research and development is a method used to produce a particular product, and test the effectiveness of the product. Results and conclusions of this study were 1) to know the implementation of career information service in SMAN 1 Ponorogo 2) the discovery of career information service model with e-Learning techniques for establishing the direction select careers class X 3) determine the effectiveness of career information service model with techniques of e-Learning to select a career direction establish class X. Keywords: career information with e-learning techniques, the students selects a career.